Akuntabilitas dan Transparansi sebagai Implementasi ISAK 35 : Tentang Penyajian Laporan Keuangan Entitas Berorientasi Nonlaba (Studi Pada Masjid Agung An-Nuur Pare Kabupaten Kediri) - Elok Oktavia Widhawati; Dwi Suhartini; Astrini Aning Widoretno (Jurnal Proaksi, 2021)
Religious organizations have a big share in the religious, social and economic life of the community, one of which is a mosque. This study aims to determine the accountability, transparency, and implementation of ISAK 35 in financial management of the Great Mosque of An-Nuur Pare, Kediri Regency. The Great Mosque of An-Nuur is a mosque that has become the central syiar of Islam in Kediri Regency, and stands under the auspices and receives cash flow from the district government. This qualitative research uses an interpretive approach to interpret and translate data so that it is easy to understand and through the case study method (direct research). The research data was obtained through direct observation (survey), interviews, and documentation. This research shows that the mosque has not achieved good accountability and transparency. In the research, it was found that the mosque did not have guidelines in making financial reports and guidelines for the implementation of organizational activities (SOP / Standard Operation Procedure), did not present complete information, and did not have an official website as a medium for information / publications widely. Even so, the mosque has carried out its responsibility in prospering the mosque through various activities. The mosque has never received input or demands from the congregation for the accountability and transparency that has been done so far. With regard to financial reports, mosque administrators still do not know and understand ISAK 35 as a guideline for reporting non-profit entities, so that financial reports are made simply. Thus, the mosque still has to improve its financial management and implement ISAK 35 as part of supporting mosque accountability and transparency. Keywords : accountability, transparency, ISAK 35